Diagnosis and Management of Heterotopic Pregnancy: A Case Report - Harnovin Kuanda; Muhamad Husen Ali; Rommy Andika Kurniawan (Indonesian Journal of Obstetrics & Gynecology Science)
Background: Heterotopic pregnancy is a rare case of pregnancy. The incident is estimated to be 1:30000 to spontaneus pregnancy. Heterotopic pregnancy is a life threatening condition to maternal and intrauterine fetus.Case Report:A 36 years old woman came with over 1 month history of amenorrhea, after being examined, her gestational age was 9-10 weeks. On 28th February 2018 patient came to PHC due to lower abdominal pain and vaginal bleeding. Ectopic pregnancy was revealed then laparotomy was performed. Then, patient came back and complained of enlarged abdomen since the laparotomy, ultrasonography examination showed intrauterine fetus. At 35 weeks gestational age, patient was undergoing cesarean section due to fetal distress.Discussion:Heterotopic pregnancy are both intrauterine and ectopic pregnancy that occur at the same time. Heterotopic pregnancy often hardly detect because of unspecific symptoms. In this case it also found difficulty in diagnosing heterotopic pregnancy, the patient was only diagnosed as ruptured ectopic pregnancy.Conclusion:Heterotopic pregnancy has a high mortality rate if the diagnosis and treatment is not done well. Ultrasonography (USG) examination has an important role in order to help diagnosing in remote area.Key words : Heterotopic pregnancy, USG, Diagnose, Treatment  AbstrakLatar belakang:Kehamilan Heterotopik adalah kehamilan yang sangat jarang terjadi, angka kejadiannya sekitar 1:30000 dibandingkan dengan kehamilan spontan. Kehamilan Heterotopik seringkali menyebabkan komplikasi yang dapat mengancam jiwa ibu dan janin.Laporan Kasus:Wanita usia 36 tahun datang dengan keluhan Amenorea lebih dari 1 bulan, setelah di periksa pasien dinyatakan hamil dengan usia kehamilan 9-10 minggu. Pada 28 februari 2018, pasien datang ke puskesmas dengan keluhan nyeri perut bawah dan keluar darah dari jalan lahir, kemudian pasien di rujuk ke Rumah Sakit. Pasien didiagnosis dengan kehamilan ektopik dan dilakukan laparotomi. Kemudian pasien  kontrol dan mengeluh perut bertambah besar pascaoperasi, dari pemeriksaan ultrasonographi didapatkan adanya janin intrauterin. Pada usia kehamilan 35 minggu dilakukan operasi caesar dikarenakan gawat janin.Diskusi:Kehamilan Heterotopik adalah kehamilan intrauterin dan kehamilan ektopik yang terjadi pada waktu yang bersamaan. Kehamilan heterotopik seringkali sulit dideteksi dikarenakan gejala yang tidak spesifik. Pada kasus ini juga ditemukan kesulitan dalam mendiagnosa kehamilan heterotopik.Kesimpulan:Kehamilan heterotopik memiliki angka mortalitas yang tinggi jika diagnosis dan tatalaksana yang dilakukan tidak baik. USG berperan penting dalam membantu penegakkan diagnosis di daerah terpencil.Kata kunci: Kehamilan Heterotopik; USG; Diagnosis; Tatalaksana